PERANCANGAN MERCHANDISE UNTUK ANNIVERSARY BIS MANIA COMMUNITY KE-12 - Wiguna, Debio Pararta; Aris Kurnia Wicaksono; Eka Wahyu Primadani; Naufal Labib (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
Bis Mania Community is a community of bus lovers, especially regional coordinators in Surabaya, which was founded in 2012. In 2024, precisely on November 10, 2024, Bis Mania Community held its 12th Anniversary in Tulungagung. In celebrating this 12th Anniversary not only organizes Family Gathering and garage visits, but the Bis Mania Community also sells various kinds of Merchandise as a medium to display identity. One of the merchandise that will be made is a T-Shirt. Merchandise offered by brands or communities in the form of T-Shirts currently has value and appeal to the community itself. Merchandise itself is a souvenir that is often found in the community as a container or means in the form of promotion of a product or brand. Merchandise itself is made with various forms or items that are commonly used daily such as T-Shirts, Tumblers, Totebags, key chains, and others. Designing a Merchandise requires research and the right illustration design so that it can attract buyers to have the merchandise. In doing the design for the Bis Mania Community Anniversary Merchandise with the theme of a vacation to the beach featuring the Object Bus, Sura and Baya Characters, and Echo Beach as the destination chosen by the Bis Mania Community. Therefore, the use of merchandise can be a souvenir that is appropriate, memorable, and as a promotional medium as well as a souvenir.